PENERAPAN MODEL PEMBELAJARAN TIME TOKEN UNTUK MENINGKATKAN KEMAMPUAN BERTANYA DAN HASIL BELAJAR KIMIA SISWA KELAS X MIPA 1 SMAN 09 KOTA BENGKULU TAHUN AJARAN 2017/2018 - Ufi Damayanti; Amrul Bahar; Salastri Rohiat (University of Bengkulu, 2020)
Research the act of this class carried out of date 01 February 2018 – 08 March 2018aims to (1) enhance the capacity of ask a student to lose their; (2) increase yields of of students to study, declaration of relinquishing his her to see liveliness of teachers and students in the process of learning to promote disorder to. A subject in this research is a student X MIPA 1 SMAN 09 city Bengkulu school year 2017/2018 on the subject of redox reactions, which amounted to 28 students. The research results show that the implementation of learning cooperative type time token can improve the ability ask students, improve learning outcomes students, and improving liveliness teachers and students in learning in subject matter reaction redoks the result of which have be completed in cycle 3rd. On the ability of cycle I ask students 75 % rate of C1, 15 % rate of C2, 10 % rate of C3 and 28,57 % student learning. Cycle II ask students 65,22 % rate of C1, 21,74 % rate of C2, 13.04 % rate of C3 with 64,29 % student learning. The cycle III ask student 4,35 % rate of C1, 78,26 % rate of C2, and 17,39 % rate of C3, with 89,29 % student learning (who has achieved indicators of the quality of the success of research and KKM). To liveliness teachers from the cycle I, II, and III each 25, 27, and 30, while liveliness students in each 21, 24, and 28